How do cinema and TV productions become ,tnemory films'? (KULT_online, 2009)
The authors of the anthology Film und kulturelle Erinnerung (Film and cultural rememberance) examine the meaning of feature fihns in contemporary memory cultures. Their views 011 the subject matter differ due to their different scientific disciplines, however, the interdisciplinary field of memory research serves as a common theoretical denominator. In terms of methodology, the contributors apply the concept of "plurimedial constellations" they developed together. This approach paves the way for a systematic analysis of "remembrance films", whose topical importance can easily be observed in today's cinema and TV productions.